A Design of Fault-Tolerant Battery Monitoring IC for Electric Vehicles Complying With ISO 26262 - Byambajav Ragchaa; Liji Wu; Xiangmin Zhang (IEEE Open Journal of Circuits and Systems)
Battery monitoring integrated circuits (BMIC) employed in the battery management system (BMS) for electric vehicle (EV) application are subjected to rigorous requirements for accuracy, reliability, and safety. This paper presents a design of an 8-cell battery pack monitoring and balancing IC, which can be stacked to monitor and balance a total of 128 cells. The design of battery cell voltage detection is realized by a second order, incremental $Σ Δ $ ADC with a high-voltage channel multiplexing scheme. The accuracy of cell voltage detection, achieved with a margin of ±10 mV, is confirmed by the test results. In this paper, we aim to enhance the reliability and robustness of the BMIC by implementing fault detection mechanisms within its circuits and incorporating fault recovery functionalities through digital circuits. To meet safety requirements, this paper adheres to the functional safety standard ISO 26262 for road vehicles. The quantitative analysis of hardware architectural metrics for the proposed BMIC demonstrates compliance with ASIL-D requirements for functional safety.